2016
DOI: 10.1108/mf-08-2014-0211
|View full text |Cite
|
Sign up to set email alerts
|

Measuring intellectual capital performance of Indian banks

Abstract: Purpose – The purpose of this paper is to measure the intellectual capital performance of Indian banks and established a relationship between intellectual capital and return on assets (ROA). The paper also compared the intellectual capital performance of public sector and private sector banks. Design/methodology/approach – This study is based on secondary data from the top 20 Indian banks. Ten banks were selected from each of the public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
74
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 37 publications
(41 reference statements)
11
74
0
1
Order By: Relevance
“…Using the large data set of 111 Pakistani financial institutions, the fixed effect and GMM regressions were applied to offer a robust relationship between IC and sustainable performance. The results reported the positive impact of IC on performance, which is consistent with many previous studies [18,27,28,30,36,37,[39][40][41]43,58,69,71,77], and also affirmed an inverted U-shaped relationship between IC and performance. This inverted U-shaped relationship is consistent with Haris, Yao, Tariq, Malik and Javaid [4] and our proposed hypothesis H 1 that financial institutions in Pakistan are capable, up to a certain level, of generating value and sustaining competitive advantage through their IC and financial capital resources.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Using the large data set of 111 Pakistani financial institutions, the fixed effect and GMM regressions were applied to offer a robust relationship between IC and sustainable performance. The results reported the positive impact of IC on performance, which is consistent with many previous studies [18,27,28,30,36,37,[39][40][41]43,58,69,71,77], and also affirmed an inverted U-shaped relationship between IC and performance. This inverted U-shaped relationship is consistent with Haris, Yao, Tariq, Malik and Javaid [4] and our proposed hypothesis H 1 that financial institutions in Pakistan are capable, up to a certain level, of generating value and sustaining competitive advantage through their IC and financial capital resources.…”
Section: Discussionsupporting
confidence: 91%
“…IC has been classified into different components and measured by different methodologies [11,13,14,16,[22][23][24][25]. However, the advanced one, i.e., value-added intellectual coefficient (VAIC), developed by Pulic [24], is used in this study as a measurement of IC.Many studies have provided evidence regarding the relationship between IC and performance in different countries [4,18,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. However, evidence from financial institutions is still scarce.…”
mentioning
confidence: 99%
“…There were many firms and researchers determined that the intellectual capital became important assets and components for the measurement of financial performances. These countries had been developed the application of intellectual capital in banking sector such as in Australia (Pulic and Bornemann, 1999); Japan (Mavridis, 2004); Malaysia (Goh, 2005);UK (El-Bannany, 2008), Hong Kong (Chan, 2009a(Chan, , 2009b and India (Singh, & Joshi, 2016).…”
Section: The Intellectual Capital and Financial Performances In Bankimentioning
confidence: 99%
“…Similarly, Kayacan and Ozkan (2015) examined the relationship on intellectual capital performance of the participation banks operated in Turkey towards the financial performances in terms of profitability ratio. Moreover, the study indicated based on the 20 banks in India whereby consists of 10 public and 10 private sector banks within the year from 2007 to 2011 (Singh et al, 2016). The last but not least, Thakur (2017) conducted the analysis on effects of intellectual capital and the financial performances of public and private sector banks in India over the period 2013 to 2015.…”
Section: The Intellectual Capital and Financial Performances In Bankimentioning
confidence: 99%
“…Weqar & Haque (2020) found that the IC of Indian CPSEs only help in enhancing its productivity, while human capital is the strongest predictor in augmenting the financial performance of the Indian CPSEs. Another study on the Indian banking industry by Singh et al (2016) found that its efficiency of IC significantly and positively influences the profitability of the Indian banks. The study on the Indian banks was also conducted by the Mondal & Ghosh (2012), and they found that both profitability and productivity is substantially and positively affected by the intellectual capital efficiency whereas ROE was not strongly influenced by the IC.…”
Section: Ic and Organisational Financial Performancementioning
confidence: 99%